The Relationship between Career Selection and Career Satisfaction - Ghaleb, Belal Dahiam Saif (PT. Riset Press International, 2024)
Career selection and career satisfaction are integral factors that influence an individual's professional development and happiness. This study examines the complex, reciprocal relationship between these two concepts through a review of relevant literature. Career choice involves determining one's future career based on interests, abilities, values, and goals. Proper career selection positively impacts career satisfaction when there is alignment between the individual and their work. Conversely, dissatisfaction with one's chosen path may precipitate career changes. Career satisfaction relates to subjective well-being and success derived from work experiences and achievement of career goals. High satisfaction promotes motivation and productivity, while low satisfaction reduces commitment and performance. Personal characteristics, educational background, socioeconomic factors, and the social environment also shape career choice and satisfaction levels over time. Compatibility between career and individual personality traits or values typically enhances outcomes. Work environment quality, development opportunities, and work-life balance further mediate this relationship. A supportive culture, continuous training, and balanced responsibilities impact job fulfillment. Informed career selection centered on self-awareness establishes foundations for satisfaction and success. However, satisfaction likewise influences persistence or diversification from initial choices. Understanding this complex, mutual relationship optimizes career trajectories and organizational effectiveness.